Engaging schools in the science of low-energy buildings - Charnley, Fiona; Fleming, Paul; Dowsett, Tony; Fleming, Margaret; Cook, Malcolm; Mill, Greig (Sage, 2012)
This article explores the relationship between the previous UK government’s initiative to rebuild and renew secondary schools, and the requirement for improved education for sustainable development in the UK. The documented research utilized a number of mechanisms to engage with pupils in Leicester city schools to increase their awareness, knowledge and understanding of the science and engineering associated with the design and operation of low-energy school buildings. Workshops, discussions with energy and sustainable development experts and inspirational visits to existing low-energy buildings were employed to develop an appreciation for the importance of energy efficiency and best design practice. The results demonstrate an increase in pupils’ knowledge and understanding of low-energy school design and additionally a rise in those pupils who are interested in science and would consider it as a career opt
Keywords: design process, education, engagement, sustainable development